The role of the class teacher as a teacher-mentor in the formation of new values and social relations among adolescents in the prevention of Internet addiction - Sereda I. N. (Scientific and Educational Areas Under Modern Challenges, 2023)
In today's world, the Internet is developing dynamically. On its basis, a special socio-cultural environment is created with its own specific content as a special social space. In this regard, the role and importance of the class teacher as a teacher-mentor, his active participation in the formation of new values and social relations in adolescents in organized activities, including in the prevention of Internet addiction, is increasing
Keywords: профилактика; классный руководитель; социальные отношения; подросток; teenager; social relations; prevention; педагог-наставник; internet addiction; интернет-аддикция; teacher-mentor; новые ценности; class teacher; new values